Methodology in educational studies - the disciplinary status and the social conditions for discussion - Piekarski, Jacek (Šolsko polje, 2012)
The methodological and theoretical problems present in the current methodological discussion in Poland are perceptible from the social and historic perspective. Some of the social conditions for the creation of knowledge and its properties, which may seem worth considering in the situation of the tendency towards building a universal area of research, are presented. The role of the methodologist and the methodology itself remains semi-independent, that is to say a separate element of the whole process of knowledge creation, a separate segment of the educational process, which, in its content, remains essentially detached from the emerging problems and experiences of those conducting the research. Recognizing the role of methodology in building a cognitive perspective and its importance for the quality of knowledge can certainly help to build communication space and create the common research practice within it.
Keywords: methodology; metodologija; knowledge; znanje; education; vzgoja in izobraževanje; society; družba; kakovost; quality